DO IT COMMITTTEE AND ERP ADOPTION AFFECT A FIRM’S PROFITABILITY? BANKING EVIDENCE FROM INDONESIA - Aninda Puji Adila; Azolla Degita Azis; Khalilul Rahman; Azla Nurul Fakhira (Bilancia : Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study is to examine the effect of the Information Technology Committee (IT Committee) and the Enterprise Resource Planning (ERP) system have affected Indonesian banking organization’s profitability as determined by Net Profit Margin (NPM). Purposive sampling was used to choose 78 samples from the research population, which consists of banks registered with the Financial Services Authority (OJK) between 2022 and 2024. Panel data regression with a Random Effects Model (REM) technique was used to evaluate the data. To verify the model's validity, descriptive statistics and traditional assumption tests, such as multicollinearity and heteroscedasticity, were carried out. The findings indicate that Net Profit Margin is not significantly impacted by either the Information Technology Committee or the ERP implementation. These results imply that the adoption of ERP systems and IT Committee frameworks has not immediately increased profitability. The low impact could be attributed to the early phases of digital transformation in Indonesian banks, organizational preparedness, and human resource skills. According to the study's findings, IT Committee and ERP adoption have limited short-term financial effects but have the ability to increase performance over the long run. It is advised that more study be done to increase the observation duration and incorporate other factors like digital maturity and cost effectiveness. Tujuan penelitian ini adalah untuk menganalisis pengaruh Komite Teknologi Informasi (IT Committee) dan sistem Enterprise Resource Planning (ERP) telah mempengaruhi profitabilitas organisasi perbankan Indonesia yang diukur melalui Margin Laba Bersih (NPM). Sampling purposive digunakan untuk memilih 78 sampel dari populasi penelitian, yang terdiri dari bank-bank yang terdaftar di Otoritas Jasa Keuangan (OJK) antara tahun 2022 dan 2024. Regresi data panel dengan teknik Model Efek Acak (REM) digunakan untuk menganalisis data. Untuk memverifikasi validitas model, dilakukan statistik deskriptif dan uji asumsi tradisional, seperti multikolinearitas dan heteroskedastisitas. Temuan menunjukkan bahwa Margin Laba Bersih tidak terpengaruh secara signifikan oleh Komite Teknologi Informasi maupun implementasi ERP. Hasil ini menunjukkan bahwa adopsi sistem ERP dan kerangka kerja Komite Teknologi Informasi belum secara langsung meningkatkan profitabilitas. Dampak yang rendah ini dapat dikaitkan dengan fase awal transformasi digital di bank-bank Indonesia, kesiapan organisasi, dan keterampilan sumber daya manusia. Menurut temuan studi, Komite IT dan adopsi ERP memiliki dampak finansial jangka pendek yang terbatas, tetapi memiliki potensi untuk meningkatkan kinerja dalam jangka panjang. Disarankan agar dilakukan studi lebih lanjut untuk memperpanjang durasi pengamatan dan memasukkan faktor lain seperti kematangan digital dan efisiensi biaya.